Simulação da implementação de usinas fotovoltaicas no anel viário que conecta a rodovia Raposo Tavares à rodovia Engenheiro Lauri Simões de Barros, em Campina do Monte Alegre (SP) - Oliveira, Mariana Fernanda de (Universidade Federal de São Carlos, 2025)
The aim of this study was to assess the potential for generating photovoltaic solar energy on the ring road that connects the Raposo Tavares highway to the Engenheiro Lauri Simões de Barros highway, located in the municipality of Campina do Monte Alegre (SP). The analysis was conducted using simulations in the System Advisor Model (SAM) software, developed by the National Renewable Energy Laboratory (NREL), a tool widely used for technical and energy modeling of photovoltaic systems. The proposal is based on taking advantage of underused areas along the ring road, characterized by being already terraced, grassed and devoid of productive or residential use. These characteristics give these areas favorable conditions for the installation of ground-mounted photovoltaic systems, with low environmental impact and reduced need for structural interventions. The simulation considered a system made up of fixed photovoltaic modules, oriented to the north, with low to medium use of the total area available. The results indicated an estimated annual generation of 403,075 kWh, enough energy to supply approximately 222 residential units, based on average national residential consumption. The data obtained shows that the use of ring roads to install photovoltaic plants represents a viable and strategic alternative for diversifying the Brazilian energy matrix. As well as contributing to the advancement of renewable energy sources, this approach allows for the efficient use and occupation of urban land, which is often idle, without compromising agricultural or environmentally sensitive areas. In addition, the study is a pioneer in the Brazilian context, since there are no consolidated records in the national literature dealing with the implementation of photovoltaic systems on ring roads. In this sense, the work serves as a starting point for future research, which could delve into the technical, economic, environmental and regulatory aspects of the proposal. The replicability of the methodology in other regions with similar infrastructure reinforces its potential for large-scale application, contributing to the consolidation of a cleaner, more resilient and decentralized energy system in Brazil, in line with the principles of sustainability and the energy transition.
Simulation of the implementation of photovoltaic plants on the ring road that connects the Raposo Tavares highway to the Engenheiro Lauri Simões de Barros highway, in Campina do Monte Alegre (SP)
Keywords: Energia renovável; Economia circular; Áreas subaproveitadas; Renewable energy; Circular economy; Underutilized areas; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENERGIZACAO RURAL; 7. Energia limpa e acessível